2000
DOI: 10.1021/ja993067z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Conformations of the Polymorphic Forms of Cimetidine from 13C Solid-State NMR Distance and Angle Measurements

Abstract: The polymorphic drug compound cimetidine, a histamine H2 receptor antagonist, was synthesized containing sites of 13C enrichment at the imidazolium methine carbon C2 and at the guanidinium methyl carbon C16. The structures of four crystalline forms of double 13C-labeled cimetidine, three anhydrates (A, B, and C) and a monohydrate (M1), were examined using 13C cross polarization magic angle spinning (CP-MAS) NMR methods. Rotational resonance magnetization exchange curves obtained for forms A and M1 were consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 42 publications
0
45
1
Order By: Relevance
“…The SSNMR analysis of forms D and E yielded spectra with very few overlapped resonances and narrow linewidths, ~0.2 ppm for 13 C (displayed in Figure 1 and Figure 2) and less than 0.8 ppm for 15 N. In both of these forms, a single resonance was observed for every 13 C and 15 N atom, consistent with a single homologous structure. N(CA)CX spectra of both these forms are displayed in Figure 5 along with the spectrum acquired on form A, highlighting the overall similarities.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…The SSNMR analysis of forms D and E yielded spectra with very few overlapped resonances and narrow linewidths, ~0.2 ppm for 13 C (displayed in Figure 1 and Figure 2) and less than 0.8 ppm for 15 N. In both of these forms, a single resonance was observed for every 13 C and 15 N atom, consistent with a single homologous structure. N(CA)CX spectra of both these forms are displayed in Figure 5 along with the spectrum acquired on form A, highlighting the overall similarities.…”
Section: Resultsmentioning
confidence: 87%
“…[14][15][16][17][18] One such study by Paulson et al showed that nanocrystalline sample preparations of ubiquitin yielded three different sets of 1 H- 15 N correlation spectra, resulting from three different polymorphs. 10 Subsequently Siedel et al assigned the C', CA and CB chemical shifts for two of these polymorphs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The shape of neopentane (CH 3 ) 4 C can be regarded as a sphere, where as pivalic acid CH 2 Cl(CH 3 ) 2 CCOOH forms dimers and therefore is cigar-like shaped. The surface of these bodys are smooth and the rotation is not sterically hindered.…”
mentioning
confidence: 99%